Design and Development of a Web-Based Attendance System Using QR Code ID Cards and Geofencing Validation - Aslina Gulo; Ritna Wahyuni; Ratu Mutiara Siregar (Academic Bright Collaboration, 2026)
Purpose – Manual attendance in plantation operations suffers from high administrative vulnerability and data fraud, creating an efficiency gap for remote work units. This study aims to develop a low-cost, web-based employee attendance information system utilizing static QR Code ID cards for Palm Oil Plant. Methods – The system was engineered using a plan-driven Waterfall lifecycle model, encompassing UML design, Laravel 10 framework implementation, a MySQL database layer, and rigorous verification via 22 granular Black Box Testing operational scenarios. Findings – The prototype successfully deployed multi-layered authentication features, returning a 100%